Endoscopic Vein Harvesting for Coronary Bypass Grafting: A Blessing or a Trojan Horse? - Ryan Accord; Jos Maessen (Cardiology Research and Practice)
Conventional open harvest of the great saphenous vein (GSV) during CABG results in approximately 7% donor-site complications. Using endoscopic vein harvesting (EVH) the full GSV length can be harvested through a 3 cm incision. This nonsystematic review discusses several key issues concerning EVH, based on an extensive Pubmed search. Found studies show that EVH results in reduced number of wound complications, less postoperative pain, earlier postoperative mobilisation, reduced length of hospital stay, and is more cost-effective. Initial studies did not find significant differences in graft histology, patency, or clinical outcome. However, in 2009 convincing evidence of inferior histological graft properties became available. Furthermore, an observational study showed that EVH resulted in significantly more graft stenosis, was associated with higher mortality, more myocard infarction, and more reinterventions. Most recent publications could not confirm these findings, however larger randomised controlled trials focusing on graft quality are being awaited.